Health and wellbeing in refugee families from Syria resettled in Denmark - Nina Odgaard Nielsen; Eirikur Benedikz; Morten Dahl; Jeanette Præstegaard; Marianne Lindahl (Elsevier, 2023)
Aims: The aim was to evaluate self-reported health status and wellbeing in a well-defined group of refugee families from Syria 2-4 years after resettlement in Denmark, and, where possible, compare it with a Danish reference population. The purpose was to determine the need for specialized health care to resettled refugees. Methods: This cross-sectional study involved 90 individuals from Syria aged 13-56 years. We used questionnaire survey to assess the general health and wellbeing in the study population in relation to a Danish reference population. Objective measurements of selected health indicators like overweight, hypertension and levels of cholesterol and blood glucose (HbA1c) were also determined for the study population. Results: Mean wellbeing scores and the proportion of study participants rating their health as good were lower among the study participants compared with the Danish population for all age groups. The proportion of participants who reported often being alone against their will was significantly higher than among Danes, as was the proportion who had nobody to talk to when having problems. A significantly higher proportion of participants experienced various forms of pain or discomfort than in the Danish population. Overall, 23.6% and 3.4% of participants had elevated cholesterol and HbA1c levels, respectively, and the prevalence of overweight (BMI ≥ 25) was 70%. Hypertension was more frequent (16.2%) than in another refugee population in Denmark (9%). Conclusions: The study demonstrated various mental and physical health challenges among the Syrian refugee families, and their health and wellbeing appeared to be substantially poorer as compared to the Danish reference population. The findings emphasize the need for systematic and specialized health care services at a municipality level to resettling refugees as a prerequisite for the refugees to become contributing citizens.